Evaporation of aqueous suspension drops with ground admixtures in the region of high-temperature combustion products; Theoretical Foundations of Chemical Engineering; Vol. 51, iss. 4 - Vysokomornaya O. V. Olga Valeryevna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Shcherbinina A. A. Anastasiya Anatolievna (2017, 2017)
Title screen